Randomized comparison of functional electric stimulation in posturally corrected position and motor program activating therapy: treating foot drop in people with multiple sclerosis - Prokopiusova, Terezie; Pavlikova, Marketa; Markova, Magdalena; Rasova, Kamila (European journal of physical and rehabilitation medicine, 2020)
BACKGROUND: Functional electric stimulation (FES) is recommended for foot drop in multiple sclerosis, although little is known about its therapeutic effect. AIM: The aim of this study is to evaluate a therapeutic effect immediately and two months after program termination (persistent and delayed effect) of a new approach using FES in combination with correcting the patients' postural system. More specifically, we evaluate the effects of this approach on the patients' clinical functions and compared it with individual physiotherapy. DESIGN: Parallel randomized blind trial. SETTING: Two-month-long treatments, functional electric stimulation in posturally corrected position (group 1) and neuroproprioceptive facilitation and inhibition physiotherapy called motor program activating therapy (group 2). POPULATION: Forty-four subjects with multiple sclerosis. METHODS: Primary outcomes: gait (the 2-Minute Walk Test; Timed 25-Foot Walk test; Multiple Sclerosis Walking Scale-12) and balance (by e.g. Berg Balance Scale [BBS], the Activities-Specific Balance Confidence Scale [ABC], Timed Up-and-Go Test [TUG]). SECONDARY OUTCOMES: mobility, cognition, fatigue and subjects' perceptions (e.g. Multiple Sclerosis Impact Scale [MSIS], Euroqol-5 dimensions-5 levels [EQ-5D-5L]). RESULTS: Group 1 showed immediate therapeutic effect in BBS (P=0.008), ABC (P=0.04) and EQ-5D-5L (self-care, P=0.019, mobility P=0.005). The improvement in EQ-5D-5L persisted and in TUG-cognitive we documented a delayed effect (P=0.005). Group 2 showed an immediate improvement in BBS (P=0.025), MSIS (P=0.043) and several aspects of daily life (the effect on health today was significantly higher than in group 1, significant difference between groups P=0.038). CONCLUSIONS: FES in the posturally corrected position has an immediate therapeutic effect on balance and patients' perceptions comparable to motor program activating therapy, and higher persistent and even delayed therapeutic effect. CLINICAL REHABILITATION IMPACT: The study results point to the importance of correcting the patients' posture when applying FES, the possibility to treat foot drop by individual physiotherapy and the activation of the patients' auto reparative processes.
Keywords: Disability Evaluation; Peroneal Neuropathies; test chůzí; Humans; Postural Balance; lidé středního věku; Multiple Sclerosis; posuzování pracovní neschopnosti; neuropatie nervus peroneus; Female; dospělí; lidé; Electric Stimulation Therapy; Gait Disorders, Neurologic; Adult; Walk Test; ženské pohlaví; Single-Blind Method; roztroušená skleróza; Male; Middle Aged; jednoduchá slepá metoda; mužské pohlaví; posturální rovnováha; neurologické poruchy chůze; elektrostimulační terapie